1990
DOI: 10.1002/cnm.1630060608
|View full text |Cite
|
Sign up to set email alerts
|

The spline finite‐strip method in the buckling analyses of thin‐walled structures

Abstract: SUMMARYA spline finite-strip method capable of analysing the buckling of prismatic thin-walled structural members under arbitrary loading is presented. It utilizes cubic B3-splines as displacement functions in the longitudinal direction and polynomials in the transverse direction. Numerical integration is used to determine the geometric stiffness matrix of the strips. Two examples which demonstrate the accuracy and versatility of the method are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The functions (x) should be modiÿed in order to satisfy the prescribed boundary conditions. This modiÿcation may be found in Reference [4]. Table I.…”
Section: Spline Functionsmentioning
confidence: 98%
See 2 more Smart Citations
“…The functions (x) should be modiÿed in order to satisfy the prescribed boundary conditions. This modiÿcation may be found in Reference [4]. Table I.…”
Section: Spline Functionsmentioning
confidence: 98%
“…This has very considerable advantages over the 'conventional' spline ÿnite strip treatment, which requires the subdivision of the plate into eight strips in order to produce solutions of comparable accuracy to those of the bubble strip method. It is worth noting that Van Erp and Meneken [4] reported that the shear local buckling coe cient of a plate with an aspect ratio of 10 was calculated as 5.30. Their study used 30 section knots with 10 ÿnite strips.…”
Section: Plates In Shearmentioning
confidence: 99%
See 1 more Smart Citation
“…Critical load includes Bifurcation point and Extreme point [5,6,7].The character of the bifurcation point is its structure have the other bifurcation of equilibrium path nearby load -displacement equilibrium path, when the load gets to critical value, if the structure or load produce a little perturbation, Load -displacement will develop along bifurcation of equilibrium path. the character of the extreme point is when the load get to critical value, if the load or displacement produces a little vary, it will respectively displacement jump and the rapid decrease of load.…”
Section: Stability Analysis Of Dump Truck Bodymentioning
confidence: 99%
“…The beam is made of material with Young's modulus E = 70960 MPa, and Poisson's ratio ν = 0.321. The beam is analyzed using 6 DEB2 elements and its lateral torsional buckling is compared with those obtained using two complicated shell models 24,25 in Table 2. Note that the difference is less than 0.2%…”
Section: Comparison With Shell Modelsmentioning
confidence: 99%